The Impact of Social Media Bullying on Mental Health in Adolescents - Indainanto, Yofiendi Indah; Purba, Arief Marizki (Indonesian Journal of Medical Anthropology, 2024)
Social media has become very interesting to use in the current digital era to interact and share information efficiently. However, the use of social media has positive and negative impacts on society, especially teenagers. Misuse of social media has negative impacts, such as the rise of bullying cases in adolescents on social media. This study aims to analyze the impact of bullying on social media on teenagers. The research method used is a descriptive qualitative research method with a literature review approach. Secondary data sources include journals, books, online media, and literature reviews. Data analysis in this study uses data reduction, data presentation, and conclusion drawing. The results stated that bullying on social media affects adolescents' mental health. The harmful perpetrators' negative behavior leads to a lack of understanding and awareness to use social media wisely. In this case, the importance of the role of the environment closest to adolescents provides education on behavior in social media and handling for victims of bullying.